(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
Marriage is an important institution that upholds societys values. Thus an important decision for any adult is to select appropriate life partner. The definition of appropriateness is largely influenced by cultural norms and values. This research was conducted to study trends in potential mate preference characteristics of the Pakistani population. To attain the aforementioned objective, an archival research was conducted. Data was collected from Sunday matrimonial sections of two most widely read newspapers (Daily Jung and Daily Dawn). Entire data was drawn for 3 decades (i.e., 1980 2009). The requirements for to-be bride and to-be grooms were noted. Result showed that in both newspapers, Physical attractiveness in to-be brides was the top sought feature in three decades, whereas for to-be grooms, working or being educated were the most required traits. It shows that most of the requirements remained same, still few changes were noted within the three decades.